Assessment of shark catches landed at PPI Ujung Serangga, Southwest Aceh - Nur Zulurrahmi; Ilham Fajri; Ratna Mutia Aprilla; Herman Herman; Rada Febriyanti; Riska Diajeng Putri (Depik, 2025)
This study aimed to assess shark catches at PPI Ujung Serangga, Southwest Aceh, focusing on species composition, size and conservation status. Data were collected through field surveys and direct measurements of sharks landed by fishers. Results showed that bottom longlines were the most widely used fishing gear and produced the highest shark catches. A total of 643 individual sharks from 16 species were identified, with the family Carcharhinidae dominating the catch. Most of the sharks caught were below gonad length (Lm), indicating the potential for juvenile shark fishing. The conservation status of sharks evaluated based on IUCN showed that most species were categorized as Near Threatened (NT) and Vulnerable (VU), with some species categorized as Critically Endangered (CR) and Endangered (EN). Almost all identified shark species are listed in CITES Appendix II. This research highlights the importance of sustainable shark fisheries management to maintain populations and biodiversity in the Southwest Aceh region.Keywords:SharkConservation StatusCITESSouthwest Aceh